Approaching the lithiation limit of MoS2 while maintaining its layered crystalline structure to improve lithium storage - Zhu, Zhiqiang (2020)
MoS2 holds great promise as high-rate electrode for lithium-ion batteries since its large interlayer can allow fast lithium diffusion in 3.0-1.0 V. However, the low theoretical capacity (167 mAh g-1 ) limits its wide application. Here, by fine tuning the lithiation depth of MoS2 , we demonstrate that its parent layered structure can be preserved with expanded interlayers while cycling in 3.0-0.6 V. The deeper lithiation and maintained crystalline structure endows commercially micrometer-sized MoS2 with a capacity of 232 mAh g-1 at 0.05 A g-1 and circa 92 % capacity retention after 1000 cycles at 1.0 A g-1 . Moreover, the enlarged interlayers enable MoS2 to release a capacity of 165 mAh g-1 at 5.0 A g-1 , which is double the capacity obtained under 3.0-1.0 V at the same rate. Our strategy of controlling the lithiation depth of MoS2 to avoid fracture ushers in new possibilities to enhance the lithium storage of layered transition-metal dichalcogenides.